Kadar dan Aktivitas Antoksidan Minuman Kunyit dan Asam yang Manis - Aisyah Tri Septiana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
The aim of this research were to know effect of curcuma and tamarind proportion and type of sugar on antioxidarit content and activity, correlation of antioxidant content and activity of curcuma and tamarind drink, and its compare with curcuma and tamarind drink commercially available. The research method was Randomized Completely Block Design (RCBD) factorial design. The trial factor were proportion of curcuma and tamarind 100 : 0, 80 : 20, 60 : 40, 40 : 60, 20 : 80, 0 : 100, respectively and type ofsugar, they were palm sugar and liquid sugar. The result of this research showed that the increase proportion of tamarind caused increase phenolic content but decrease of ascorbic acid content and curcumin absorbance of the drink The increasing proportion of tamarind to 20 percent on curcuma gave increase antioxidant activity but the increasing proportion of tamarind from 40 to 100 percent decrease antioxidant activity. Compare with palm sugar, increasing liquid sugar increased ascorbic acid content and antioxidant activity. There was correlation between antioxidant content and antioxidant activity.